Effectiveness of E-Court in Handling Civil Cases in Class IA Religious Court of Ternate - Yunus, Yahya; Arsad, Jamal Hi; Hardina, Hardina; Ramon, Tomás Mateo; Budiono, Arief (Law and Justice, 2024)
E-Court is a court instrument made by the Indonesian Supreme Court which provides services to society in the forms of online registration, payment, summoning, and courts based on the Supreme Court Decision No. 1 of 2019. Objective: The problems of this research are: (1) How is the effectiveness of the e-Court application in the procedural processes in the Class I A Religious Court of Ternate City and (2) What are the obstacles that influence the application of e-Court in the Class I A Religious Court of Ternate City. Method: This was empirical research which used the statute approach and the case approach. In this research, researchers used the live case study approach which was applied to a legal phenomenon with an ongoing process. Results: showed that the e-Court implementation is effective. Its application is already according to the goal of Article 2 clause (4) of Law No. 48 of 2009 on Judicial Power. The e-Court provides a simpler, quicker, and cheaper form of civil case resolution. The obstacles in e-Court include a lack of human resources, inadequate internet facilities, and social culture. An improvement of the network and socialization on the e-Court implementation under the jurisdiction of the Class I A Religious Court of Ternate are needed. Function: This paper provides information on the effectiveness of the e-Court application. Novelty: This paper provides novelty as no previous research has studied the effectiveness of the e-Court application in the procedural processes in the Class I A Religious Court of Ternate City.   E-Court adalah instrumen pengadilan yang dibuat oleh Mahkamah Agung RI yang memberikan pelayanan kepada masyarakat berupa pendaftaran, pembayaran, pemanggilan, dan persidangan secara online berdasarkan Perma No. 1 Tahun 2019. Tujuan: Permasalahan dari penelitian ini adalah: (1) Bagaimana efektivitas penerapan e-Court dalam proses beracara di Pengadilan Agama Kelas I A Kota Ternate dan (2) Apa saja kendala yang mempengaruhi penerapan e-Court di Pengadilan Agama Kelas I A Kota Ternate. Metode: Penelitian ini merupakan penelitian empiris yang menggunakan pendekatan perundang-undangan dan pendekatan kasus. Dalam penelitian ini, peneliti menggunakan pendekatan studi kasus langsung yang diterapkan pada suatu fenomena hukum dengan proses yang sedang berlangsung. Hasil: menunjukkan bahwa penerapan e-Court sudah efektif. Penerapannya sudah sesuai dengan tujuan Pasal 2 ayat (4) UU No. 48 Tahun 2009 tentang Kekuasaan Kehakiman. E-Court memberikan bentuk penyelesaian perkara perdata yang lebih sederhana, cepat, dan murah. Hambatan dalam e-Court antara lain kurangnya sumber daya manusia, fasilitas internet yang belum memadai, dan budaya masyarakat. Perlu adanya peningkatan jaringan dan sosialisasi mengenai penerapan e-Court di wilayah hukum Pengadilan Agama Ternate Kelas I A. Fungsi: Penelitian ini memberikan informasi tentang efektivitas penerapan e-Court. Kebaruan: Tulisan ini memberikan kebaruan karena belum ada penelitian sebelumnya yang mengkaji tentang efektivitas penerapan e-Court dalam proses beracara di Pengadilan Agama Kelas I A Kota Ternate.